Математическая модель низковольтной электрической линии с распределенной нагрузкой - Байда, Е.И.; Гапоненко, Г.Н. (Електротехніка і електромеханіка, 2011)
In the article, a mathematical model of a low-voltage power circuit with consumers distributed along the line is introduced. The electric circuit and the model application examples are presented.